Individual Freedom and Netizen Presence As Others in Tiktok Social Media Creator Content Message Delivery - SETIAWATI, Amalia; RONDA, Mirza; SERAN, Alexander (PT Keberlanjutan Strategis Indonesia, 2023)
This research is focused on interactions on social media TikTok, where researchers raise issues regarding individual freedom and the presence of other people in conveying messages on social media TikTok. Based on some circumstances, the researcher sees a transition in the meaning of individual freedom and the presence of other people in the context of interaction on social media TikTok. The rationale for this study is that researchers use the perspective of freedom and the presence of other people, according to Jean-Paul Sartre, which is then studied through the theory of symbolic interactionism (George Herbert Mead) and self-presentation theory (Erving Goffmann). The paradigm used in this study is the postmodern paradigm, in which researchers attempt to deconstruct the meaning of individual freedom and the presence of other people in conveying messages on social media TikTok. The key informants in the study were two content creators of the TikTok social media who were selected purposively. The results of the study show that the skills of TikTok social media creators are needed in negotiating individual freedom agreed upon by netizens and managing the presence of other people (netizens) to interact on TikTok social media in order to achieve goals, one of which is building social capital, monetization, and social transformation.